This is factorial and means (n-1)(n-2)(n-3).........[n-(n-2)][n-(n-1)] = (n-1)!
i.e 5! = 1 x 2 x 3 x 4 x 5 = 120 6!/5! = 6 in the same way (n-1)! can be expressed as n!/n
Factorials are widely used in Combinatorics to calculate probabilities.
This is factorial and means (n-1)(n-2)(n-3).........[n-(n-2)][n-(n-1)] = (n-1)!
i.e 5! = 1 x 2 x 3 x 4 x 5 = 120 6!/5! = 6 in the same way (n-1)! can be expressed as n!/n
Factorials are widely used in Combinatorics to calculate probabilities.
"It's easy to have faith in yourself and have discipline when you're a winner, when you're number one. What you've got to have is faith and discipline when you're not yet a winner." Vince Lombardi
How to write a lazy proof
Teaching yourself how to prove
There are currently 1 users browsing this thread. (0 members and 1 guests)